2005
DOI: 10.1111/j.1744-6570.2005.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Impression Management Use and Effectiveness Across Assessment Center Exercises: The Role of Competency Demands

Abstract: We report 2 studies that examine how promotional candidates use verbal and nonverbal impression management (IM) tactics across several structured assessment center exercises that differ in the competency demands they place on candidates. Based on the competency-demand hypothesis (Shoda, Mischel, & Wright, 1993a, 1993b, it was predicted that IM use would occur most frequently and have the strongest effects on assessor evaluations in exercises that place greater demands on candidates' interpersonal skills than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 62 publications
4
52
1
Order By: Relevance
“…The implication is that if those with low ATIC were not producing behaviour to match the station dimension, they could reduce the negative impact on their performance by high use of IM. However, although the benefit of IM has been demonstrated in past research (e.g., Kleinmann & Klehe, 2011;McFarland et al, 2005;Stevens & Kristof, 1995), the current study shows that its positive effect is limited for those with high ATIC. The nonverbal IM assessed in this study may not necessarily be perceived by applicants or interviewers as a negative behaviour, given that doctors are expected to display positive interpersonal communication like maintaining eye contact (Weissmann et al, 2006).…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…The implication is that if those with low ATIC were not producing behaviour to match the station dimension, they could reduce the negative impact on their performance by high use of IM. However, although the benefit of IM has been demonstrated in past research (e.g., Kleinmann & Klehe, 2011;McFarland et al, 2005;Stevens & Kristof, 1995), the current study shows that its positive effect is limited for those with high ATIC. The nonverbal IM assessed in this study may not necessarily be perceived by applicants or interviewers as a negative behaviour, given that doctors are expected to display positive interpersonal communication like maintaining eye contact (Weissmann et al, 2006).…”
Section: Discussioncontrasting
confidence: 74%
“…McFarland et al (2005) demonstrated this effect, showing that higher use of impression management tactics (smiling, eye contact, ingratiation) resulted in higher ratings of technical performance regardless of actual job knowledge. This rating effect may be particularly likely in those interviewing potential medical students, given that competent use of nonverbal communication is itself considered an important skill for doctors (Weissmann, Branch, Gracey, Haidet, & Frankel, 2006).…”
Section: A Moderator Of the Effect Of Atic On Selection Performancementioning
confidence: 88%
See 2 more Smart Citations
“…At this point, FLEs have to communicate with customers in order to better understand their needs and conditions, for which reason they have to possess the necessary social skills. The questionnaire surveys also show that in customised services, FLEs are required to have higher levels of social skills, again confirming scholarly empirical research (McFarland, Yun, Harold, Viera, & Moore, 2005).…”
Section: Customisation Influences the Level Of Social Skills Requiredsupporting
confidence: 67%